2003
DOI: 10.1108/01443580310455241
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic variables and the Malaysian equity market

Abstract: Analyzes dynamic linkages between stock prices and four macroeconomic variables for the case of Malaysia using standard and well-accepted methods of cointegration and vector autoregression. Empirical results suggest the presence of a long-run relationship between these variables and the stock prices and substantial short-run interactions among them. In particular, documents positive short-run and long-run relationships between the stock prices and two macroeconomic variables. The exchange rate, however, is neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
144
4
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(181 citation statements)
references
References 43 publications
29
144
4
4
Order By: Relevance
“…This is also true only for the first sub-sample (1988)(1989) but all the variables were co integrated with stock prices for the second (1990)(1991)(1992) and third sub-samples (1993)(1994)(1995). Nevertheless, in general, Ibrahim and Aziz (2003), Booth and Booth (1997), Wongbanpo and Sharma (2002), Chen (2003), Chen et al (2005) and Mukherjee and Naka (1995) reveal that the rate of inflation, money growth, interest rates, industrial production, reserves, and exchange rates are the most popular significant factors in explaining the stock market movement. However, empirical studies by Barrows and Naka (1994) conclude that inflation has negative effects on the stock market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is also true only for the first sub-sample (1988)(1989) but all the variables were co integrated with stock prices for the second (1990)(1991)(1992) and third sub-samples (1993)(1994)(1995). Nevertheless, in general, Ibrahim and Aziz (2003), Booth and Booth (1997), Wongbanpo and Sharma (2002), Chen (2003), Chen et al (2005) and Mukherjee and Naka (1995) reveal that the rate of inflation, money growth, interest rates, industrial production, reserves, and exchange rates are the most popular significant factors in explaining the stock market movement. However, empirical studies by Barrows and Naka (1994) conclude that inflation has negative effects on the stock market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, two popular measures of aggregate economic activity (real GNP and industrial production) do not appear to be related with stock returns. Ibrahim and Aziz (2003) investigate the relationship between stock prices and industrial production, money supply, consumer price index, and exchange rate in Malaysia. Stock prices are found to share positive long-term relationships with industrial production and CPI.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The authors concluded that the variables are unrelated in the short run for the countries that they selected. In Malaysia context, (Ibrahim and Aziz, 2003) employed cointegration analysis and Vector Auto Regression modeling with using monthly data from January 1977 to August 1998 to investigate the interactions between Malaysian equity market and four macroeconomic variables: real output, price level, money supply and exchange rate. They observed that unstable interactions between the stock prices and exchange rates existed during that crisis period.…”
Section: Literature Reviewmentioning
confidence: 99%